Biodegradable polyurethane/graphene oxide scaffolds for soft tissue engineering: in vivo behavior assessment. Issue 17 (21st November 2020) - Ivanoska-Dacikj, Aleksandra; Bogoeva-Gaceva, Gordana; Krumme, Andres; Tarasova, Elvira; Scalera, Chiara; Stojkovski, Velimir; Gjorgoski, Icko; Ristoski, Trpe
Abstract: In this work, 3D porous electrospun scaffolds based on DegraPol ® (DP), a polyester urethane, with different concentrations of graphene oxide (GO) (0.0–2.0 wt%) were obtained. In order to produce scaffolds with increased porosity, solutions of DP and GO were co-electrospun with polyethylene oxide (PEO), which was subsequently removed. The electrospinning resulted in the formation of porous and fibrous scaffolds with superior elasticity. The colloidal Ag was successfully used as a novel method of scaffold sterilization. The results of the in vivo analysis showed scaffold degradation, absence of an inflammatory process and penetration of tissue cells in the scaffold. GRAPHICAL ABSTRACT: